From America to the World: Protestant Christianity's Creation of Religious Liberty - Peter A. Lillback (Reformed Center for Religion and Society, 2015)
ABSTRACT:Â Half the population of the world to this day still has not experienced religious freedom. Religious persecution often still occurs at many places in the world. Research studies show that there is a direct correlation between religious freedom and economic prosperity.